IMPLEMENTASI TEKNIK MODELING UNTUK MENINGKATKAN KEMAMPUAN SOSIAL ANAK USIA DINI - LUBIS, MASRIDAH (UNISAN JURNAL, 2025)
Social is learning to understand problems and ways Modeling Techniques, Social Skills to solve them. The aim is to master understanding and proficiency in social problems. The phenomenon that occurs in The kindergarten class at Darul Ulum Tanjung Heran demonstrates a relatively low level of social skills. This condition is evident from student behaviors such as frequently disturbing their peers, reluctance to engage in social interactions, unwillingness to share, and the lack of evident development in empathy. Therefore, an intervention strategy is required to enhance the students’ social skills, one of which is the application of modeling techniques. The purpose of this study is to examine the development of students’ social skills through the implementation of modeling techniques. This research employs a qualitative descriptive approach. The subjects of the study are students from the Darul Ulum Kindergarten class who fall into the low category in terms of social competence. Data collection techniques used in this study include interviews, observations, and documentation. Based on the results of the study, it can be concluded that the teacher, acting as a model in class B2, applied several stages in the modeling process, namely: attention, stimulus, production, motivation, and reinforcement. The implementation of these stages has proven to facilitate the teacher in developing the social skills of students in class B2. The modeling technique in fostering students’ social abilities has been shown to be effective in nurturing, developing, and significantly enhancing the quality of their social skills.